Book Review: Theologi Penginjilan - Aritonang, Arthur (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
This book review discusses the results of Stephen Tong's research on the theology of evangelism, hereafter referred to as ST. The research is motivated by the phenomenon that Christian communities often find themselves trapped between two extremes. On one hand, there are churches that tend to be rational and focus on worldly aspects, human organization, economics, administration, and tradition, thereby neglecting the spiritual concerns of the congregation. On the other hand, there are churches that prioritize liturgy, emotional satisfaction, and individual experiences, but abandon rigorous theological thinking and biblical teaching. From these two extremes, ST finds a third way, namely, a church that seriously studies biblical truth while carrying out the Great Commission of Jesus Christ. This evangelistic effort must combine theology and evangelism, which is referred to as the reformed evangelical movement. This book is presented to provide the Christian congregation with a correct understanding of the theology of evangelism. The fundamental questions posed by ST are: what is evangelism? Who is eligible to go evangelizing? The conclusions of this research are: (1) Evangelism is the proclamation of the good news of Christ's redemption as the core of Christian faith to all humanity. (2) Those who have experienced salvation from God in Jesus Christ and are eager to share what they know with others, have a strong commitment to learn about the theology of evangelism, and are willing to go evangelizing.